Sequential Scalp Assessment in Hair Regeneration Therapy Using an Adipose-Derived Stem Cell–Conditioned Medium. Issue 6 (June 2020) - Narita, Keigo; Fukuoka, Hirotaro; Sekiyama, Takuya; Suga, Hirotaka; Harii, Kiyonori
Abstract : BACKGROUND: An adipose-derived stem cell–conditioned medium (ADSC-CM) reportedly exerts skin-rejuvenating and hair growth-promoting effects. In the therapeutic application of ADSC-CM for alopecia, changes to the interfollicular scalp remain unclear although some evidence has indicated hair growth-promoting effects. OBJECTIVE: To evaluate the effects of ADSC-CM not only on hair follicles, but also on the interfollicular scalp. METHODS: Forty patients (21 men, 19 women; age range, 23–74 years) with alopecia were treated by intradermal injection of ADSC-CM every month for 6 months. Eighty fixed sites on patients were investigated by trichograms, physiological examinations, and ultrasonographic examinations at 4 time points (before treatment and 2, 4, and 6 months after the initial treatment). RESULTS: Hair density and anagen hair rate increased significantly. As physiological parameters, transepidermal water loss value gradually increased, with significant differences at 4 and 6 months after the initial treatment, but hydration state of the stratum corneum and skin surface lipid level showed no obvious changes. As ultrasonographic parameters, dermal thickness and dermal echogenicity were increased significantly. CONCLUSION: Intradermal administration of ADSC-CM on the scalp has strong potential to provide regenerative effects for hair follicles and the interfollicular scalp. An adipose-derived stem cell–conditioned medium offers a promising prospect as an alternative treatment for alopecia.